Case Study of Dispute Resolution Due to Force Majeure and Covid 19 - Muhammad Nawawi (ISNU Sumatera Utara, 2024)
This study analyzes the settlement of default disputes due to force majeure and the COVID-19 pandemic, which have caused delays in the implementation of contractual obligations. The background of this study focuses on the impact of COVID-19 as a force majeure event that affects various business sectors and causes the inability of parties to fulfill their obligations. The research method used is normative juridical, with an analytical approach to relevant legal regulations and case studies to understand the implementation of the law in force majeure situations. The results of the study show that COVID-19 is widely recognized as a legitimate reason for delaying obligations based on the principle of force majeure. The dispute resolution process often involves negotiation, mediation, or arbitration as an alternative to formal litigation. The conclusion of this study emphasizes the importance of force majeure provisions in contracts and flexibility in dispute resolution. Dispute resolution outside the courts, through mediation or arbitration, is often more efficient and solution-oriented than litigation. This study recommends that contracts include clear force majeure clauses and encourage the use of alternative methods to resolve disputes, in order to maintain fair and sustainable business relationships in the future.